The Library of Congress, Collections Security and the Role of its Inspector General - Schornagel, Karl W. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The Inspector General of the Library of Congress discusses the Library's collections security program and how his office manages audits and investigations.